‘’ROLE OF ILLUSTRATIVE PICTURES IN THE UNDERSTANDING OF A TEXT DURING A READING FOR COMPREHENSION LESSON, CASE OF 3RD FORM AT ‘’COMPLEXE SCOLAIRE LA RECONNAISSANCE DE KANANGA’’ - Théophile, MAMBA KATAYI (IJRDO - Journal of Social Science and Humanities Research, 2023)
We were concerned to find a strategy that could facilitate the understanding of the text for students, that of associating illustrative images with a text in order to capture the attention of a reader; then led to determine whether illustrative images are effective in improving learners’ reading comprehension ability. Thanks to qualitative and quantitative analysis methods, we conducted our surveys with two groups of 65 students, the first called "experimental of 30 students" and the second "control of 35"; all subjected to the Pretest, Test and Post-test, the first was evaluated on the basis of texts with images, and achieved an average score of 61.8, while the second was evaluated on the basis of texts without images and obtained 50.8. in the student’s t test, the difference between the two means proved to be significant at the threshold of 0.01, i.e. tobs (4.47) >ttab(2.66), which led to rejecting H0, and confirming our hypotheses. Therefore, the experimental group performed itself better than the control group, one understood the texts better than the other, thanks to the association of illustrative images.